1991
DOI: 10.1002/jcu.1870190203
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound of the common bile duct in patients undergoing cholecystectomy

Abstract: One hundred patients undergoing cholecystectomy underwent ultrasonography of the biliary tree on the day prior to surgery. At operation a per-operative cholangiogram was performed unless stones were palpable in the duct. Pre-operative biliary ultrasonography accurately identified dilatation of the common bile duct (sensitivity 96%, specificity 95%) but was less accurate at detecting common duct stones (sensitivity 36%, specificity 98%). Thirty three percent of patients with dilated ducts on ultrasound did not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
41
0
8

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(51 citation statements)
references
References 13 publications
0
41
0
8
Order By: Relevance
“…Current advanced optical imaging modalities cannot image through more than 5 mm of fat or require exogenous contrast agents [7][8][9]. Non-optical imaging modalities such as ultrasound can see through the fat, but have lower resolution and probes are typically too large for laparoscopic insertion [10,11]. Surgeons need a laparoscopic, non-invasive optical imaging modality which allows them to locate these ducts and other critical anatomy when embedded in fat.…”
Section: Introductionmentioning
confidence: 99%
“…Current advanced optical imaging modalities cannot image through more than 5 mm of fat or require exogenous contrast agents [7][8][9]. Non-optical imaging modalities such as ultrasound can see through the fat, but have lower resolution and probes are typically too large for laparoscopic insertion [10,11]. Surgeons need a laparoscopic, non-invasive optical imaging modality which allows them to locate these ducts and other critical anatomy when embedded in fat.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 ). Moreover, clinical studies have suggested low sensitivity (25-82%) and limited specificity (56-100%) of TUS when detecting bile duct stones [2][3][4][5][6] . It's reported positive and negative predictive values are 69% and 78%, respectively 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Dies ist damit zu erklären, dass ein Teil dieser Befunde auch bei extrabiliären Erkrankungen wie Pankreatitis, Zirrhose oder Herzinsuffizienz zu finden ist. Gallengangssteine lassen sich mit der konventionellen Sonographie nicht mit genü-gender Sicherheit diagnostizieren (Sensitivität 36%), bei hinreichendem Verdacht muss eine Abklärung mithilfe der endoskopischen retrograden Cholangiographie (ERC;[33]) erfolgen. PTC).…”
unclassified